ANALISIS KEPUASAN NASABAH TERHADAP PELAYANAN FRONTLINER BANK X KANTOR CABANG KHUSUS SUDIRMAN - Andani Fauzita Vidyandari; Matunun Parulian Hutagaol; Joko Affandi (School of Business, Bogor Agricultural University (SB-IPB), 2021)
Abstract: Customer satisfaction is the key to a service company's success, especially in the banking industry with its increasingly fierce competition. Customer satisfaction is measured by staff services, where interaction between customers and staff is the key. Unsatisfactory frontline staff's (forntliner) services can lower the bank's image in customers' eyes. This study aimed to analyze customer satisfaction with the frontliner's services at Bank-X official branch of Sudirman. The data were collected using a questionnaire with a convenience sampling technique to select the respondents. The analysis method used was SERVQUAL method and gap analysis where customer satisfaction would be known from the difference between customer perceptions of received service with customer expectations. The results showed that customer expectations were higher than perceptions of the frontliner's services, but that did not mean that Bank X's frontliner's services were of poor quality. Respondents who chose Bank X as the main bank compared to other banks and the Cartesius diagram results showed no need to improve service attributes, showing that the customer's opinion on the service is already good. The majority of the respondents' characteristics were office workers, highly educated, and earn more than 5 million rupiahs would certainly have high aspirations. Therefore their expectations of service would also be higher. What needs to be done by Bank X's frontliners is to maintain the quality of existing services and cut down the waiting time for customers by installing the self-service system. Keywords: customer satisfaction, frontliner, gap analysis, Importance Performance Analysis, SERVQUAL